2017
DOI: 10.2337/db17-0086
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 Attenuates Development of Type 2 Diabetes via Improvement of Islet β-Cell Function and Survival

Abstract: Growth differentiation factor 11 (GDF11) has been implicated in the regulation of islet development and a variety of aging conditions, but little is known about the physiological functions of GDF11 in adult pancreatic islets. Here, we showed that systematic replenishment of GDF11 not only preserved insulin secretion but also improved the survival and morphology of β-cells and improved glucose metabolism in both nongenetic and genetic mouse models of type 2 diabetes (T2D). Conversely, anti-GDF11 monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 50 publications
6
53
0
3
Order By: Relevance
“…Garcia-Ocana et al reported a complex role for hepatocyte growth factor (HGF) signaling in β-cell apoptosis 54,55 . A recent study reported the role of growth differentiation factor 11 (GDF11) in β-cell apoptosis via actions on TGF-β/Smad2 signaling 56 . Activin receptor-like 7 (ALK7) has also been linked to apoptosis via Smad2 and Caspase-3 30,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Ocana et al reported a complex role for hepatocyte growth factor (HGF) signaling in β-cell apoptosis 54,55 . A recent study reported the role of growth differentiation factor 11 (GDF11) in β-cell apoptosis via actions on TGF-β/Smad2 signaling 56 . Activin receptor-like 7 (ALK7) has also been linked to apoptosis via Smad2 and Caspase-3 30,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Afamin has been associated with both prevalent and incident T2DM in a large-scale pooled study of eight prospective cohorts 33 and we here obtain support from both two-and one-sample MR analyses for it to play a causal role in the disease. Less is known about the function of the other two proteins; inhibin β C is one of the inhibin/activin hormones and is highly expressed in liver whereas WFIKKN2 is known to bind GDF8/11 proteins with high affinity 34 , both of which have been implicated in diabetes 35,36 . We and others have shown that genetic variants in the WFIKKN2 region regulate serum GDF8/11 levels in trans via WFIKKN2 protein levels 14,19 and previously noted a correlation between WFIKKN2 and GDF8/11 serum levels 14 , however in the current study we did not find a significant association between GDF8/11 and T2DM so additional studies are required to understand the mechanisms by which WFIKKN2 may affect risk of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the analysis of the protein measurements, we applied a Yeo-Johnson transformation on the protein data to improve normality, symmetry and to maintain all protein variables on a similar scale 40 35 . Logistic regression was run for all 4,782 SOMAmers targeting 4,137 human proteins for incident or prevalent T2DM as outcome, with age and sex included as covariates, and an additional model including BMI.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were fixed in 4% formaldehyde, then sectioned and stained with H&E or van Gieson (VG). The immunofluorescence staining of pancreatic tissues was performed as previously reported (Li et al, ). Livers were frozen at −80°C and stained with oil red O or ROS fluorescent probe‐dihydroethidium.…”
Section: Methodsmentioning
confidence: 99%